Pengaruh Kualitas Produk, Harga dan Testimonial terhadap Keputusan Pembelian Sepeda Listrik di Surabaya - Irma Kariri Ngadang; Anita Asnawi; Mochammad Arfani; Liling Listyawati (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study is designed to explore the extent to which product quality, price, and testimonials influence consumer purchasing decisions for electric bicycles in the city of Surabaya. The growing awareness of environmentally friendly transportation has driven the expansion of the electric bicycle market in urban areas. A quantitative approach was employed through a survey method, with data collected using closed-ended questionnaires distributed to 100 electric bicycle consumers. The independent variables in this research include product quality (X1), price (X2), and testimonials (X3), while the dependent variable is purchasing decision (Y). The results of multiple linear regression analysis reveal that, collectively, the three independent variables significantly influence consumer purchasing decisions (F = 153.218; p < 0.001). However, when examined individually, only testimonials showed a statistically significant effect (p < 0.001), while product quality and price did not exhibit a meaningful influence (p > 0.05). The coefficient of determination (R²) was found to be 0.827, indicating that the model explains 82.7% of the variation in purchasing decisions. The findings highlight testimonials as the most dominant factor (β = 0.679), suggesting that businesses should adopt digital testimonial-based marketing strategies to strengthen consumer trust.